Visible-Light-Driven Selenyl-Radical-Mediated Cascade Spirocyclization of 3-(2-Isocyanobenzyl)indoles with Diselenides - Cao, Tong-Yang; Qi, Lin; Dong, Yi-Chen; Cao, Jie-Hui; Wang, Li-Jing (Synlett, 2023)
We present a facile, visible-light-driven, selenyl-radical-mediated, cascade spirocyclization of 3-(2-isocyanobenzyl)indoles with diselenides that affords various selenylated spiro[indole-3,3′-quinoline] derivatives under mild conditions. This protocol has good functional-group tolerance and a broad substrate scope; both diaryl and dialkyl diselenides are tolerated.
Keywords: photochemical reaction; visible light; cascade reaction; spirocyclization; spiroindolequinoline selenides; diselenides